A membrane capture assay for lipid kinase activity - Knight, Zachary A (2007)
Phosphoinositide kinases such as PI3-kinase synthesize lipid second messengers that control diverse cellular processes. Recently, these enzymes have emerged as an important class of drug targets, and there is significant interest in discovering new lipid kinase inhibitors. We describe here a procedure for the high-throughput determination of lipid kinase inhibitor IC(50) values. This assay exploits the fact that phosphoinositides, but not nucleotides such as ATP, bind irreversibly to nitrocellulose membranes. As a result, the radiolabeled lipids from a kinase assay can be isolated by spotting the crude reaction on a nitrocellulose membrane and then washing. We show that diverse phosphoinositide kinases can be assayed using this approach and outline how to perform the assay in 96-well plates. We also describe a MATLAB script that automates the data analysis. The complete procedure requires 3–4 h.